2008
DOI: 10.1088/0256-307x/25/9/019
|View full text |Cite
|
Sign up to set email alerts
|

A Kind of Exact Inflationary Solution in the Chaotic Inflation Model to Non-minimally Coupled Scalar Field

Abstract: We present a kind of exact inflationary solution in the chaotic inflation scenario to non-minimal coupled scalar field, taking the Hubble parameter directly as a function of the scalar field ϕ, H(ϕ) = αϕ n . Using the analysis of the WMAP3 data, we give the range of power index n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[32], the Eqs. (23) and (24) can be decoupled, and then the equation of motion for the curvature perturbation becomes…”
Section: Cosmological Perturbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32], the Eqs. (23) and (24) can be decoupled, and then the equation of motion for the curvature perturbation becomes…”
Section: Cosmological Perturbationsmentioning
confidence: 99%
“…For this inflationary model, it can be found that only a very small range of the values of the parameter ξ is allowed for high values of the parameter n (see also Refs. [23,24]). Also, Futamase and Maeda [17] considered a chaotic inflationary scenario in models having non-minimal coupling with curvature in the context of power law inflation.…”
Section: Introductionmentioning
confidence: 99%